2003
DOI: 10.1007/s00262-003-0385-8
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of a single peritumoural dose of IL-2 on transplanted murine breast cancer

Abstract: Interleukin-2 therapy is not clearly effective against breast cancer both in mouse models and in human patients. However, the study of IL-2 therapy of breast cancer remains important, as 3,700 women died from this malignancy in the Netherlands in 2000. Previously we have shown the therapeutical efficacy of a single peritumoural IL-2 application in different experimental models and in veterinary patients. Here we apply this mode of IL-2 therapy to advanced mouse mammary carcinoma models, i.e., severe metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Recipients received 10 6 tumor cells of slowly growing spontaneous mammary adenocarcinoma obtained from syngeneic females as described previously [6]. On the next day after transplantation, experimental animals received single injection of plant peptide extracts (1 mg in 0.1 ml saline) to the site of transplantation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recipients received 10 6 tumor cells of slowly growing spontaneous mammary adenocarcinoma obtained from syngeneic females as described previously [6]. On the next day after transplantation, experimental animals received single injection of plant peptide extracts (1 mg in 0.1 ml saline) to the site of transplantation.…”
Section: Methodsmentioning
confidence: 99%
“…Three perpendicular sizes of the tumor were measured and its mean diameter was calculated from these values for each recipient [6]. The results were evaluated using Student's t test.…”
Section: Methodsmentioning
confidence: 99%
“…melanoma, pulmonary metastasis of renal carcinoma, unresectable pancreatic head carcinoma and malignant mesothelioma. In contrast, IL-2 therapy for breast cancer has not been generally effective although, recently, peri-tumoural administration of IL-2 was reported to significantly improve survival in mice with advanced and relatively aggressive tumours (45). Furthermore, in a phase-I trial with HER2-overexpressing metastatic breast cancer, Repka and colleagues (46) reported encouraging results when Trastuzumab was used in combination with IL-2.…”
Section: Cytokines With Potential Prognostic and Therapeutic Rolesmentioning
confidence: 99%
“…Finally, the entire complex of inherent attributes of human BC is hardly reproduced in one mouse strain/model. Hence, we developed a system of mouse models with different characteristics and natural incidences of mammary cancer to reproduce various forms of human BC [20][21][22]. Recently, we have reported about our mouse models as appropriate tools to test alternative novel modes of anti-BC therapy [8,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we developed a system of mouse models with different characteristics and natural incidences of mammary cancer to reproduce various forms of human BC [20][21][22]. Recently, we have reported about our mouse models as appropriate tools to test alternative novel modes of anti-BC therapy [8,21,22]. Transplantable aggressive mouse mammary carcinoma in A/Sn mice demonstrated high metastatic spread to liver, spleen, kidney, and lymph nodes comparable with human BC [21].…”
Section: Introductionmentioning
confidence: 99%